Rights, Camera, action a short advocacy feature on the harassment of bit players in the Philippines - Dionisio, Armina Louise; Lucena, Styephanie Louise B.; Mandal, Cristel Maureen T. (2016.)
Harassment among bit players in the Philippines is evident yet remains largely undiscussed within and outside the media industry. In the 2013 socio-realist Ekstra, a typical day of a marginalized bit player was portrayed. This study intended to determine the level of consistency of the scenes in Ekstra that depict harassment of bit players to actual film production practices. Moreover, this research aimed to know which type of harassment is the most occurring among bit players. Using a descriptive content analysis, the researchers also classified the types of harassment that are apparent in the film. Interview questions were developed from the selected scenes. Semi-standardized type of interview was used to gather data from actual bit players. Research results show that only three (3) out of nine (9) selected scenes that depict harassment of bit players are highly consistent to actual film production practices. These three are classified under noncompliance of just and favourable conditions in the workplace; and violation to agree upon fees waged to bit players. As an output, this study produced a two-minute short advocacy feature to communicate the data gathered from the content analysis of the film Ekstra and series of interviews that proves the consistency of the scenes to actual film production practices pertaining to harassment of bit players in the country.
Thesis -- Bachelor of Arts in Communication and Media Studies. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Ekstra; Harassment; Bit players; Film production practices